ANALISIS PENGARUH CUACA TERHADAP EFISIENSI PANEL SURYA GRID TIE MENGGUNAKAN KONFIGURASI MICRO INVERTER DAN STRING INVERTER TERHADAP ENERGI YANG DIHASILKAN - Setyo, Purnomo; Yanuar Zulardiansyah, Arief; Ariep, Jaenul; Sinka, Wilyanti (Universitas Nusa Cendana, Indonesia, 2023)
The grid-tie PLTS system in the installation process can be carried out with a micro-inverter and string-inverter configuration. This research uses an experimental method by taking measurements of voltage, current, power, electrical energy (kWh), and power factor at predetermined measurement points. The analysis was carried out in various weather conditions, whether sunny, cloudy, or rainy, to obtain the efficiency performance of the electrical energy produced, and tests were carried out on both configuration models to obtain significance values for these two configurations. The data analysis shows that micro-inverters perform better in various weather conditions and have a significant difference compared to string-inverters of 9.93%. In sunny weather conditions, the micro-inverter also produces better electrical power by 20.43%. On the other hand, in cloudy weather conditions, the string-inverter configuration produces a better electrical power performance of 14.97%. Photovoltaic modules with a micro-inverter configuration have an average efficiency of 10.03% - 11.4%, while string inverters have an average efficiency of 7.17% - 9%. The power factor of the micro-inverter configuration is 0.35, and the string-inverter has a power factor of 0.4.